dx(3x+2y+1)-dy(3x+2y-1)=0

Simple and best practice solution for dx(3x+2y+1)-dy(3x+2y-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for dx(3x+2y+1)-dy(3x+2y-1)=0 equation:


Simplifying
dx(3x + 2y + 1) + -1dy(3x + 2y + -1) = 0

Reorder the terms:
dx(1 + 3x + 2y) + -1dy(3x + 2y + -1) = 0
(1 * dx + 3x * dx + 2y * dx) + -1dy(3x + 2y + -1) = 0

Reorder the terms:
(1dx + 2dxy + 3dx2) + -1dy(3x + 2y + -1) = 0
(1dx + 2dxy + 3dx2) + -1dy(3x + 2y + -1) = 0

Reorder the terms:
1dx + 2dxy + 3dx2 + -1dy(-1 + 3x + 2y) = 0
1dx + 2dxy + 3dx2 + (-1 * -1dy + 3x * -1dy + 2y * -1dy) = 0

Reorder the terms:
1dx + 2dxy + 3dx2 + (-3dxy + 1dy + -2dy2) = 0
1dx + 2dxy + 3dx2 + (-3dxy + 1dy + -2dy2) = 0

Reorder the terms:
1dx + 2dxy + -3dxy + 3dx2 + 1dy + -2dy2 = 0

Combine like terms: 2dxy + -3dxy = -1dxy
1dx + -1dxy + 3dx2 + 1dy + -2dy2 = 0

Solving
1dx + -1dxy + 3dx2 + 1dy + -2dy2 = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'd'.
d(x + -1xy + 3x2 + y + -2y2) = 0

Subproblem 1

Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0

Subproblem 2

Set the factor '(x + -1xy + 3x2 + y + -2y2)' equal to zero and attempt to solve: Simplifying x + -1xy + 3x2 + y + -2y2 = 0 Solving x + -1xy + 3x2 + y + -2y2 = 0 Move all terms containing d to the left, all other terms to the right. Add '-1x' to each side of the equation. x + -1xy + 3x2 + y + -1x + -2y2 = 0 + -1x Reorder the terms: x + -1x + -1xy + 3x2 + y + -2y2 = 0 + -1x Combine like terms: x + -1x = 0 0 + -1xy + 3x2 + y + -2y2 = 0 + -1x -1xy + 3x2 + y + -2y2 = 0 + -1x Remove the zero: -1xy + 3x2 + y + -2y2 = -1x Add 'xy' to each side of the equation. -1xy + 3x2 + y + xy + -2y2 = -1x + xy Reorder the terms: -1xy + xy + 3x2 + y + -2y2 = -1x + xy Combine like terms: -1xy + xy = 0 0 + 3x2 + y + -2y2 = -1x + xy 3x2 + y + -2y2 = -1x + xy Add '-3x2' to each side of the equation. 3x2 + y + -3x2 + -2y2 = -1x + xy + -3x2 Reorder the terms: 3x2 + -3x2 + y + -2y2 = -1x + xy + -3x2 Combine like terms: 3x2 + -3x2 = 0 0 + y + -2y2 = -1x + xy + -3x2 y + -2y2 = -1x + xy + -3x2 Add '-1y' to each side of the equation. y + -1y + -2y2 = -1x + xy + -3x2 + -1y Combine like terms: y + -1y = 0 0 + -2y2 = -1x + xy + -3x2 + -1y -2y2 = -1x + xy + -3x2 + -1y Add '2y2' to each side of the equation. -2y2 + 2y2 = -1x + xy + -3x2 + -1y + 2y2 Combine like terms: -2y2 + 2y2 = 0 0 = -1x + xy + -3x2 + -1y + 2y2 Simplifying 0 = -1x + xy + -3x2 + -1y + 2y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

d = {0}

See similar equations:

| 0.11y+0.09(y+4000)=1950 | | -15=-7+2x | | 0.11y+0.09(y+4000)=7000 | | (3+5b)+7= | | 7+2x=4x-2 | | (13+a)=15 | | 6x+4-3x=16 | | 5(v-6)-7v=-14 | | x+12+29=80 | | 4-6(w+z)=10 | | 9a-15=30 | | 12x+29=80 | | x+x+2=145 | | x+2+x=145 | | -2*3x+1-2x=-4*2x-4 | | -11/13x=2 | | 6(3-4t)=-12(2t-3/2) | | 11/13x=2 | | 3.2=2v | | 3w^2+6w-16=0 | | 2x-570+x=1992 | | -6(x+2)-x-8=-7(x+4)+8 | | 3=u/3.84 | | 3y^2-4=12 | | 12=2/5y | | -18+4f+18f=20f+18 | | -12+2p=-18 | | 1/2(12-9n)=4-3n | | 11=2-q | | -4(b+1)+2b=3(2n-1) | | 7+2j=3j | | 3(5s+5)-6s=3(3s+1)-5 |

Equations solver categories